Encapsulation of clove oil in nanostructured lipid carriers from natural waxes: Preparation, characterization and in vitro evaluation of the cholinesterase enzymes - Meneses, Alessandra Cristina de (2018)
Eugenol is a phenolic compound largely found in the clove essential oil that possesses promising biological activity. However, its low water solubility is a major concern and encapsulation is an alternative to improve water affinity. The objective of this work was to produce nanostructured lipid carriers (NLC) by hot homogenization/ultrasound emulsification and to evaluate the effect of free and encapsulated clove oil on the in vitro cholinesterase enzymes modulation using Drosophila melanogaster (DM) tissue. The NLC composed of a natural wax (carnauba or beeswax) and crodamol showed an average diameter between 121 and 367 nm with good dispersion and colloidal stability. The spherical shape and solid character together with the semi-crystalline environment confirm the formation of NLC. DSC analysis indicated polymorphic transition events of the waxes. In vitro tests using DM demonstrated that free clove oil showed a good inhibition of the butyryl and acetylcholinesterase enzymes above a concentration of 10 mM, with IC50 values of 4.3 and 3.5 mM, respectively. The dispersions of the NLC loaded with clove oil showed a decrease in the IC50 enzymes values, indicating the preservation of the clove essential oil and suggesting an increased in the solubility. Results indicate that NLC dispersions have good potential to be used for foods and cosmetic aqueous formulations possessing biological activity.